Dynamic improvisation capabilities as a learning mechanism in early internationalizing firms - Chetty, Sylvie; Gabrielsson, Peter; Gabrielsson, Mika (Elsevier, 2024)
Our study addresses an inconsistency in the literature on whether a lack of knowledge in early internationalizing firms is an obstacle or an advantage. We integrate learning, capabilities, and improvisation literature to reveal how case firms from New Zealand and Finland internationalize early under uncertainty and time pressure. We develop a process model and propositions to show how firms develop improvisation capabilities and subsequently rapidly acquire the international business knowledge that can explain early internationalization. Improvisation and the associated rapid learning complement the learning advantage of newness with an alternative explanation for early internationalization.
Keywords: Capabilities; Foreign market entries; Uncertainty; learning; internationalisation; improvisation; fi=Kansainvälinen liiketoiminta|en=International Business|